Determination of Gender using Discriminant Analysis of Hand Dimensions among Adult Participants - Rahman, Syed Azizur; Shukla, Kamlesh Kumar; Mishra, Pankaj Kumar; Singh, Ranjana (Indian Journal of Community Health, 2023)
Background: The estimation of gender using hand dimensions is a crucial role in forensic investigation and legal sciences. Objectives: In this study, the mean score of hand measurements have been derived and linear discriminant analysis has been applied to predict gender from hand dimensions. An Independent t-test has been employed to know discrimination between male and female. The accuracy of gender estimation has been derived and checked by ROC curve. Material and Methods: A sample of 150 participants has been collected for the completion of this study, where 78 males and 72 females were found aged between 18 and 24 years. The breadths and lengths of left and right hands of the participants have been measured. Results: Respondents’ mean score of length and breadth of left hand were found 17.69 ± 1.30 and 7.56 ± 1.17, respectively. It was found to be significantly different in the respondents’ mean scores of males and females. Conclusions: The hand dimensions of males were higher than females. The prediction of a number of females and males were 76 and 74, respectively, and its accuracy was observed 0.87. This research can be applied for larger sample and would be helpful in predicting gender discrimination among adults through hand dimensions.